Multiple Tooth-Rowed Parareptile From the Early Permian of Oklahoma - Rowe, Dylan C. T.; Scott, Diane M.; Bevitt, Joseph J.; Reisz, Robert R. (Frontiers in Earth Science, 2021)
The Dolese Limestone Quarry near Richards Spur, Oklahoma includes an elaborate system of caves which have been infilled with early Permian fossil rich sediments. In operation for more than a century, the quarry yielded vast numbers of disarticulated skeletal elements of the most diverse assemblage of fully terrestrial tetrapods from the Paleozoic. Excavations carried out in this century are distinct in producing large numbers of articulated and semiarticulated skeletons, including numerous new taxa. Dolese is therefore unique among early Permian localities in being home to a diverse assemblage of small parareptiles, including two species of Delorhynchus. Here we describe a new species of acleistorhinid, characterized by the presence of multiple tooth rows on the dentary, that can be identified with confidence as a third new species of Delorhynchus. The multiple tooth rowed condition is deemed not to be a pathological condition, and appears to have formed in the same manner as in the captorhinid eureptile Captorhinus aguti through uneven growth of the tooth-bearing element.